PERAN KARANG TARUNA DALAM MEMECAHKAN MASALAH SOSIAL DI DESA WARNASARI - candra kerti, fariq mahesa; Nur Faizah, Rahayu; Keisha Az Zahra, Revania; Siti Nurhasanah, Nabila; Perona Siregar, Rheind (Universitas Merdeka Madiun, 2024)
The role of youth social organizations is crucial in triggering social change, enhancing collective awareness, and advancing community welfare across Indonesia. One such organization is Karang Taruna, which provides a platform for village youth to actively participate in local development. Warnasari Village in Pangalengan, Bandung Regency, West Java, offers an interesting study of how Karang Taruna plays a role in addressing social issues and promoting progress at the local level. With unique social, cultural, and geographical characteristics, an ethnographic review can provide a deep understanding of social structures, interaction dynamics, and challenges faced by Karang Taruna in Warnasari Village. This research aims to provide a holistic understanding of the roles, internal dynamics, and contributions of Karang Taruna in solving social problems and enhancing local community welfare. The results of this study are expected to offer valuable insights for policymakers, decision-makers, and development practitioners interested in sustainable development programs based on local community participation.